Social Media Dependency and Work-Related Attitudes with Religiosity Mediation - Hassan Asaari, Muhammad Hasmi Abu; Desa, Nasina Mat; Arshad, Mohd Anuar; Mohamad Noor, Mohamad Muzammil (European Scientific Journal, ESJ, 2022)
The paper explores the social media dependency and work-related attitudes about religiosity as a mediator among employees in public and private organizations. Not many studies explore the above variables especially in the context of Malaysian employees. Self-administered questionnaires were distributed among employees in the public and private organizations in the selected major cities in the country. Data analyses are conducted using SPSS, namely reliability analysis, correlation analysis, regression analysis, and mediation analysis. Interestingly, the paper only discovers religiosity has a positive impact on work-related attitudes among employees in public and private organizations. Unfortunately, the other hypotheses are not supported and no mediation of religiosity on social media dependency and work-related attitudes was discovered. Further analysis is conducted on religiosity as moderator; the result also shows no moderation of religiosity on social media dependency and work-related attitudes. Discussions on the results are elaborated accordingly.